2014 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP) 2014
DOI: 10.1109/icassp.2014.6855104
|View full text |Cite
|
Sign up to set email alerts
|

Performance analysis of MAX-SINR algorithm under CSI mismatch

Abstract: With interference alignment (IA), the achievable degrees of freedom (DoF) in wireless networks can be linearly scaled up with the number of users. However, to attain full DoF, the availability of perfect network channel state information (CSI) is mandatory, which impedes the practical deployment of IA since only partial network CSI may be accessible. In this paper, we investigate the effect of CSI mismatch on the performance of maximum signal-to-interference-plusnoise ratio (Max-SINR) algorithm. We show that w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…However, as stated in [6], [21], [22], Max-SINR without orthogonalization can not achieve full DoF, since at least one of its precoders and/or combiners may become rankdeficient, and this can further result in reduced multiplexing gain. Therefore, when using Max-SINR, if the goal is to preserve full DoF, the inclusion of orthogonalization steps is mandatory.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as stated in [6], [21], [22], Max-SINR without orthogonalization can not achieve full DoF, since at least one of its precoders and/or combiners may become rankdeficient, and this can further result in reduced multiplexing gain. Therefore, when using Max-SINR, if the goal is to preserve full DoF, the inclusion of orthogonalization steps is mandatory.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been shown that these inserted orthogonalization steps do not compromise the achievable sum rates even at intermediate SNRs [21]. Consequently, in the sequel, we use Max-SINR with orthogonalization which can be represented as follows [22]:…”
Section: Discussionmentioning
confidence: 99%